Iskazivanje vjere na radnom mjestu / Freedom of Religion in the Workplace: Presude Evropskog suda za ljudska prava o predstavkama muslimanskih apelanata / Decisions of the European Court of Human Rights on Applications of Muslim Appellants - Begović, Nedim (Context: Journal of Interdisciplinary Studies, 2022)
This article contains an overview of potential conflicts between manifestation of religion through performing Islamic rituals and contractual obligations in the workplace as well as some difficulties which members of Muslim communities in European countries, including Bosnia and Herzegovina, face in their endeavour to harmonize religious obligations and duties at the workplace. The focus of article is the analysis of case-law of former European Commission and actual European Court of Human Rights concerning accommodating Islamic worship in the workplace. The Author argues that monitoring bodies of the European Convention on Human Rights hitherto did not provide adequate incentives to country contracting parties to the Convention to accommodate Islamic ritual practice in the workplace. Given this circumstance, the author is of the opinion that the protection of religious expression in the workplace should be provided in the first place by domestic legislation. The opportunity for this he sees in the adoption of appropriate provisions on the protection of the right of Muslims to manifest their religion in the workplace within the contractual regulation of relations between Bosnia and Herzegovina and the Islamic Community.